RANCANG BANGUN MESIN PENGERING KOTORAN HEWAN SISTEM TUNGKU PEMANAS MENGGUNAKAN SOLAR CELL 50 Wp - Asep Rachmat; Gunawan, Ade (Universitas Majalengka, 2025)
This study aims to design and develop a chicken manure drying machine powered by a 50 Wp solar panel. The system stores energy in a 12V battery and converts it through a 1500W inverter to operate four 50W heating lamps. The main objective is to reduce the high moisture content in raw chicken manure, making it suitable for use as organic fertilizer. The design process included field surveys, literature review, and component calculations. Experimental testing showed that the machine successfully reduced the initial moisture content from 31% to 13% within 6 hours at a controlled temperature of 43°C. These results indicate that the solar-powered drying system is effective and energy-efficient for small-scale organic fertilizer production.